The exposure to volatile organic compounds associate positively with overactive bladder risk in U.S. adults: a cross-sectional study of 2007–2020 NHANES - Zhang, Dawen; Yan, Ziyi; He, Junhao; Yao, Yunmin; Liu, Kai (Frontiers in Public Health, 2024)
Objective The aim of this study was to comprehensively investigate the potential relationship between blood volatile organic compounds (VOCs) and overactive bladder (OAB) risk. Methods A total of 11,183 participants from the 2007–2020 National Health and Nutrition Examination Survey (NHANES) were included in this cross-sectional study. We used multivariate logistic regression models to investigate the relationship between nine blood VOCs and OAB risk. Restricted cubic spline (RCS) analysis was used to investigate the dose-response relationship between blood VOCs and OAB. In addition, the overall association of blood VOCs with OAB risk was assessed by weighted quantile sum (WQS) regression model. Finally, we conducted subgroup analyses to explore the findings in different high-risk populations. Results After adjusting for potential confounders, logistic regression analysis revealed that blood 2,5-dimethylfuran (aOR = 2.940, 95% CI: 1.096–7.890, P = 0.032), benzene (aOR = 1.460, 95% CI: 1.044–2.043, P = 0.027) and furan (aOR = 9.426, 95% CI: 1.421–62.500, P = 0.020) were positively independent associated with the risk of OAB. And dose-response risk curves indicated that 2,5-dimethylfuran, benzene and furan in the blood were linearly positive associated with OAB risk. WQS regression analysis showed that exposure to mixed blood VOCs increased the risk of OAB (OR = 1.29, 95% CI: 1.11–1.49), with furans having the greatest weight. In subgroup analyses, we found that OAB was more susceptible to blood VOCs in young and middle-aged, male, non-hypertensive, and alcohol-drinking populations. Conclusions The results of this study indicate that high exposure to VOCs is independently and positively associated with OAB risk in U.S. adults, particularly 2,5-dimethylfuran, benzene, and furan. In addition, age, gender, hypertension and alcohol consumption may influence the association. Our study provided novel epidemiologic evidence to explore the potential role of environmental pollutants in OAB.